Food packaging bags based on thermoplastic corn starch reinforced with talc nanoparticles - Lopez, Olivia Valeria (2014)
Packaging bags from thermo-compressed films of thermoplastic corn starch containing talc nanoparticles (0, 1, 3 and 5% w/w) were developed. Mechanical properties of films were studied by two different techniques (tensile tests and quasi-static assays) revealing starch films reinforcement by talc addition. Strength improvement of thermoplastic starch films with talc concentration higher than 3% w/w was reflected in an increase in both Young?s modulus and yield stress. Talc particles modified failure mode of thermo-seal of thermoplastic starch films giving another bags opening possibility. Usually, bags based on starch films could be only opened by tearing while those of starch-talc bionanocomposites could be torn or peeled off. Finally, in order to evaluate packaging bags tightness, films barrier properties were determined. Water vapor and oxygen permeability were reduced 54 and 26%, respectively, by talc addition (3% w/w) to thermoplastic starch.